Luktevannshus og snusdåser - Berg, Marit Elida Angell (Tidsskrift for kulturforskning, 2009)
The article discusses human beings’ concept of smell in Europe and Norway during the time period 1770 to 1820. It particularly focuses on the perception of fragrance and stench. The basis for the discussion is two small and decorative artifacts from Norsk Folkemuseum’s collections: a scent container and a snuff box, both in silver. These types of items were often used to exchange gifts between a man and a woman at engagements or weddings. Earlier research on these artifacts has focused on aspects like shape, style, material properties or their significance as gifts. This article takes on a more in-depth analysis to reveal in what types of cultural settings scent containers and snuff boxes were used. In order to understand why scent containers and snuff boxes were used, it is necessary to know the types of scents people of that era were surrounded by. Likewise, knowledge of the actual scent of the content in the scent containers and snuff boxes is necessary. The article discusses whether scent containers and snuff boxes were used in different social classes, and whether both men and women used them. The article concludes that scent containers and snuff boxes were used in situations that required protection from stench, both in the private and the public sphere.